Efektivitas Inovasi Pendaftaran Haji Melalui Aplikasi Haji Pintar Di Kantor Kementrian Agama Kota Bekasi - Krishantoro Krishantoro; Diana Prihadini; Aramia Fachria; Alfiyani Dewi Rakadita (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to analyze of Hajj registration trough the Smart Hajj Application at the office of the Ministry of Religion of Bekasi City. This research methos used descriptive qualitative. This is a research method that produces data based on the idea that realy is not an objective formation, but is constructed through a process of interaction in community and cultural groups. The smart hajj application at the Bekasi City Ministry of Religion has been really effective. The obstacle of the smart hajj application is that there are frequent disturbances in the smart hajj application system, making it difficult for prospective pilgrims to access it. Efforts are being made to upgrade the smart hajj application system and add new features.